2004
DOI: 10.1007/s00330-004-2517-8
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization alone and in combination with other therapies: a comparative study in an animal HCC model

Abstract: The purpose of this study is to compare transarterial chemoembolization (TACE) alone and in combination with other therapies in an animal model. Subcapsular implantation of a solid Morris hepatoma 3924A in the liver was carried out in 50 male ACI rats (day 0). Tumor volume (V1) was measured by MRI (day 13). After laparotomy and retrograde placement of a catheter into the gastroduodenal artery (day 14), the following protocols of the interventional procedure were applied: TACE (mitomycin C + lipiodol) + immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…immunotherapy or antiangiogenesis therapy) seemed to retard tumor growth compared with TACE alone in a recent HCC animal model study [22]. When considering hyperthermic ablations, the aim of blood flow occlusion in the tumor region is to decrease heat dispersion enforced by the blood stream and, therefore, to increase the size of the necrosis area induced by RFA [23].…”
Section: Discussionmentioning
confidence: 98%
“…immunotherapy or antiangiogenesis therapy) seemed to retard tumor growth compared with TACE alone in a recent HCC animal model study [22]. When considering hyperthermic ablations, the aim of blood flow occlusion in the tumor region is to decrease heat dispersion enforced by the blood stream and, therefore, to increase the size of the necrosis area induced by RFA [23].…”
Section: Discussionmentioning
confidence: 98%
“…Meta-analyses of data from multiple trials have shown that chemoembolization improves the survival of patients with unresectable HCC and may become the standard treatment [36,37]. In an animal study, it could be demonstrated that the combination of TACE with immune and antiangiogenesis therapy results in reduced tumor growth compared with TACE alone [38]. This might be a possible therapeutic option in the future.…”
Section: Discussionmentioning
confidence: 97%
“…Although surgical approaches such as liver resection and transplantation are considered the most effective treatments to cure HCC, a large portion of patients are unsuitable candidates for these approaches due to the development of multicentric tumors, extrahepatic metastases and early vascular invasion, in addition to a shortage of donor organs, a high complication rate and comorbidities (28)(29)(30)(31)(32). Local methods of tumor ablation including TACE, percutaneous ethanol injection, radiofrequency ablation (33)(34)(35), microwave coagulation therapy and laser-induced thermotherapy are commonly used (36).…”
Section: Discussionmentioning
confidence: 99%